AN EFFECT OF STORAGE AND TRANSPORTATION TEMPERATURE ON QUANTITATIVE AND QUALITATIVE COMPOSITION OF MICROFLORA OF PLANT PRODUCTS - S. V. Avilova; V. N. Kornienko; A. A. Gryzunov; A. A. Vankova (Пищевые системы)
The results of the study on changes in the composition and quantity of epiphytic and endophytic microorganisms of plant products during storage and transportation are presented. For the investigation, the authors took apple fruits and leafy spicy green products that had biological peculiarities and allowed investigating processes of the long-term and short-term main stages (cold storage, transportation by refrigerated transport, presales storage) of the continuous cold chain on the way to a consumer. Apple fruits were placed in storage in cold chambers with the temperature regimes of plus (2–3)°C and minus (1–2)°C, where they were stored for 90 days. The vegetative organs of dill and parsley were transported during 8 hours by a refrigerated truck and placed in the commercial refrigeration equipment at two temperature regimes (4–5) C and (0–1) C for 72 hours for presales storage. The results of the microbiological analysis showed that the number of endophytic microorganisms (bacteria, yeasts and molds) was lower by 1–3 orders of magnitude in apple fruits and by 2–3 times in green vegetables compared to the number of epiphytic microorganisms. It was established that the regime of storage at negative temperatures completely inhibited the development of epiphytic bacteria on fruits, significantly delayed the multiplication of epiphytic yeasts and molds; while at a positive temperature the number of bacteria increased approximately by 10–17 times, yeasts by 180 times and molds by 3 times. The dynamics of changes in the number of endophytic microorganisms during storage showed the same trend that was observed for epiphytic microorganisms. Analysis of the microbial quantity after transportation of green products showed an increase in abundance of the revealed groups of epiphytes and endophytes by 1.5–3 times upon absolute prevalence of bacteria. After short-term storage, a significant growth of the revealed microbial groups was found; with that, their quantity was 1.5–6.5 times higher at (4–5) C than at (0–1) C. The authors experimentally confirmed the conclusion that with respect to reduction of losses due to microbiological spoilage and extension of shelf life, the cold storage regime of the studied plant products at near-zero temperatures is preferable compared to the regimes of storage at higher positive temperatures.